Pengaruh Model Pembelajaran Guided Inquiry Dipadu Two Stay Two Stray (TSTS) Terhadap Keterampilan Proses Sains Siswa Pada Materi Larutan Asam Basa Terintegrasi Pendidikan Lingkungan Hidup - Hadits Rafidah Deli; Agung Purwanto; Darsef Darwis (LPPM Universitas Negeri Jakarta, 2017)
This study aims to determine the effect of the application of guided inquiry model combined with the Two Stay Two Stray (TSTS) on the students' science process skills on the acid-base solution materials integrated with environmental education. The method used is Quantitative Quasi-Experiment method use Posttest Only Nonequivalent Control Group Design. The subjects consisted of science students from grade 11 classes as a control and as an experimental class which amounted to 36 students in each class. The instrument used in this research is rubric of science process skill with the scale of assessment 1 to 4 and result of learning (posttest) in the form of multiple choices. The average score of science process skill of control class students is 2.8 whereas experimental class is 3.1 with a good category. Based on the statistical analysis, it is found that there is difference of students' science process skill in control class and experiment class (tcount = 7.14, ttable = 1.66 then tcount> ttable), so it can be concluded that the guided inquiry model combined with TSTS has a positive effect on science process skill on the material of acid-base solution integrated with environmental education. Keywords: Science Process Skills, Guided Inquiry, Acid-Base Solutions, TSTS